2022
DOI: 10.1093/jmammal/gyac028
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a population of leaf-eared micePhyllotis vaccarumabove 6,000 m in the Andes and a survey of high-elevation mammals

Abstract: Biologists have long pondered the extreme limits of life on Earth, including the maximum elevation at which species can live and reproduce. Here we review evidence of a self-sustaining population of mice at an elevation that exceeds that of all previously reported for mammals. Five expeditions over 10 years to Volcán Llullaillaco on the Argentina/Chile border observed and collected mice at elevations ranging from 5,070 m at the mountain’s base to the summit at 6,739 m (22,110 feet). Previously unreported evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Our discovery highlights the value of conducting surveys in inaccessible, poorly explored regions of South America, and suggests that the Andean Altiplano is a region where much work is still needed to reduce the Linnean and Wallacean shortfalls for native small mammals (Storz et al 2020;Rengifo et al 2022). With our new record of Punomys, the number of living mammal species and genera in Chile now stands at 170 and 88, respectively Rodríguez-San Pedro et al 2022, 2023Quiroga-Carmona et al 2022). Recent additions to the Chilean mastofauna have been based on descriptions of new species (e.g., Abrothrix manni and Dromiciops bozinovici and D. mondaca; D' Elía et al 2015Elía et al , 2016a, as well as range extensions for previously described species (e.g., Eumops perotis, Histiotus laephotis, Notiomys edwardsii, Nyctinomops aurispinosus, Oligoryzomys flavescens; Ossa et al 2015;D'Elía et al 2016b;Rodríguez-San Pedro et al 2022, 2023Quiroga-Carmona et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our discovery highlights the value of conducting surveys in inaccessible, poorly explored regions of South America, and suggests that the Andean Altiplano is a region where much work is still needed to reduce the Linnean and Wallacean shortfalls for native small mammals (Storz et al 2020;Rengifo et al 2022). With our new record of Punomys, the number of living mammal species and genera in Chile now stands at 170 and 88, respectively Rodríguez-San Pedro et al 2022, 2023Quiroga-Carmona et al 2022). Recent additions to the Chilean mastofauna have been based on descriptions of new species (e.g., Abrothrix manni and Dromiciops bozinovici and D. mondaca; D' Elía et al 2015Elía et al , 2016a, as well as range extensions for previously described species (e.g., Eumops perotis, Histiotus laephotis, Notiomys edwardsii, Nyctinomops aurispinosus, Oligoryzomys flavescens; Ossa et al 2015;D'Elía et al 2016b;Rodríguez-San Pedro et al 2022, 2023Quiroga-Carmona et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, high-elevation surveys in the Central Andes have revealed how much we have yet to learn about the elevational range limits of small mammals. For example, mountaineering mammal surveys of multiple volcanoes in the Chilean Puna de Atacama have documented evidence of the Andean leaf-eared mice, Phyllotis vaccarum (previously referred as to P. xanthopygus rupestris ), living at elevations >6000 m (Storz et al 2020; Steppan et al 2022), and mammal surveys in the Andean Altiplano of northwestern Argentina have documented surprisingly diverse rodent assemblages at elevations >4000 m (Urquizo et al 2022). Thus, as part of a continuing effort to further redress Linnean and Wallacean shortfalls for Andean small mammals, here we report the first Chilean record of the genus Punomys , a record that also significantly extends the elevational and latitudinal range of Punomys .…”
Section: Introductionmentioning
confidence: 99%
“…These results support the integration between different aspects of the phenotype since a higher degree of behavioral variation seems to be related to a lower physiological versatility. Both P. vaccarum and A. andina are among the mammals with the widest altitudinal distribution worldwide (Patterson et al, 2015; Steppan et al, 2022; Steppan & Ramirez, 2015; Storz et al, 2020) and, in the Central Andes, both of them successfully cope with a wide range of environmental conditions. Based on the observations reported here, we infer that different strategies uphold their adaptation to environmental variability: while in P. vaccarum it would occur mainly via physiological flexibility, in A. andina it would occur mainly via behavioral flexibility.…”
Section: Discussionmentioning
confidence: 99%
“…It occupies altitudes ranging from 800 m to more than 6700 m a.s.l. (Steppan & Ramirez, 2015; Storz et al, 2020), which makes it the world's highest elevation‐dwelling species, not only for mammals but also for all vertebrates (Steppan et al, 2022). Regarding its diets, it has been observed that different populations alternate between herbivorous (López‐Cortés et al, 2007), frugivorous‐granivorous, and omnivorous (Sassi et al, 2017) habits.…”
Section: Methodsmentioning
confidence: 99%
“…In combination with the live-captured specimen of Phyllotis vaccarum from the summit of Volcán Llullaillaco (6739 m) 4 , the vouchered summit mummies from 6029-6233 m represent the highest elevation mammal specimens on record. Video records, evidence of active burrows, and various lines of indirect evidence indicate that Phyllotis mice occur at elevations >6000 m on Llullaillaco and neighboring Volcán Socompa 4,25,26 . Thus, the highest records of Phyllotis (and the only physical records of wild mammals from elevations >6000 m) are all from the summits of Andean peaks within a section of the Central Volcanic Zone in the Puna de Atacama, between latitudes of 24°S and 28°S, South of the Tropic of Capricorn.…”
Section: New Elevational Records For Wild Mammalsmentioning
confidence: 99%